Mediating the relationship between parental control/support and offspring delinquency: self-efficacy for a conventional lifestyle versus self-efficacy for deviance - Walters, Glenn D. (Crime & delinquency, 2018)
This study sought to determine whether self-efficacy for a conventional lifestyle mediated the relationship between parental control/support and offspring delinquency using longitudinal data supplied by 2,252 (1,145 boys, 1,107 girls) high school students surveyed in the 10th, 11th, and 12th grades. The results of a three-regression negative binomial analysis revealed that self-efficacy for a conventional lifestyle mediated the relationships between Wave 1 parental monitoring and attachment, on one hand, and Wave 3 delinquency, on the other hand. Comparison pathways mediated by self-efficacy for deviance, consistent with predictions, did not achieve significance. These results indicate that a social cognitive variable, self-efficacy for a conventional lifestyle, may be partially responsible for the delinquency-inhibiting effects of parental control (monitoring) and support (attachment).